A2.9 High Serum-Cholesterol Levels by Either Low Density Lipoprotein Receptor Deficiency or a Cholesterol-Rich Diet Result in Synovial Activation and Osteophyte Formation During Experimental Osteoarthritis. (25th February 2013) - Munter, W de; Slöetjes, AW; Walgreen, B; Helsen, MM; Berg, WB van den; Lent, PL van
Abstract : Background and Objectives: Atherosclerotic studies show that scavenger receptors on macrophages are capable of taking up oxidised low density lipoprotein (oxLDL), resulting in increased inflammatory properties of the macrophage. Accumulated LDL can be oxidised in an inflammatory milieu such as OA, possibly resulting in oxLDL uptake of synovial macrophages. We investigated whether increased LDL levels lead to more severe OA pathology in experimental induced OA. Materials and Methods: LDL receptor deficient (LDLr -/- ) mice and their wild type (WT) controls received either a cholesterol-rich or control diet for 120 days. Experimental OA was induced by intra-articular injection of collagenase. 36 days after OA induction, mice were sacrificed and total knee joints and serum were collected. Bone marrow derived cells were differentiated into type two macrophages and pre-incubated with oxLDL for 24 hours and stimulated with S100A8. RNA was analysed for gene expression. Data are depicted as mean ± SEM. Results: WT mice receiving a normal diet developed moderate cartilage destruction (6.1 ± 1.5), synovial thickening (1.4 ± 0.2) and osteophyte formation (32.4 µm 2 ± 14.6). Serum LDL levels were significantly higher in LDLr -/- mice compared to WT mice (7.33 mmol/L ± 0.46 and 0.54 mmol/L ± 0.04 respectively; p < 0.05), which was additionally increased by a cholesterol-rich diet (38.73 mmol/L ± 3.11; p < 0.0001). Despite differences in serum LDL levels, no significant differences between the four groups were found regarding synovial thickening and cartilage destruction. Expression of S100A8 by the synovial lining, however, was increased after receiving a cholesterol-rich diet, suggesting synovial activation. Furthermore, a cholesterol-rich diet increased ApoB accumulation in synovial lining macrophages of LDLr -/- mice. Interestingly, at the tibial plateau, LDLr -/- mice showed almost a fourfold increase of osteophyte formation compared to WT mice (206.3 µm 2 ± 36.3; p < 0.05). When receiving a cholesterol-rich diet, osteophyte formation at the lateral side of the tibial plateau in LDLr -/- mice further increased from 107.0 µm 2 ± 49.3 to 309.4 µm 2 ± 41.7 (p < 0.05). In vitro stimulation of oxLDL-laden macrophages with S100A8 showed a significant decrease of IL-10 expression and an increase of BMP6 expression compared to macrophages that were not pre-incubated with oxLDL. Conclusions: Increased serum cholesterol levels by either LDL receptor deficiency or a cholesterol-rich diet increase oxLDL uptake by synovial lining macrophages and synovial activation. In accordance with in vitro data, this synovial activation by oxLDL leads to an inflammatory milieu with increased S100A8 levels, resulting in increased osteophyte formation.